Estimation of Rental Rates of Assets in Public Service Agencies Using Alternative Methods - Dhian Adhetiya Safitra; Akhmad Khabibi; Roy Anshor (Universitas Ahmad Dahlan, Yogyakarta, 2026)
Asset optimization is an increasingly important issue for Indonesia’s Public Service Agencies (PSAs), which are required to determine fair and transparent rental values for state-owned assets (SOAs). This research develops an alternative rental-pricing framework for recreational sports assets, using a mini soccer field at the Polytechnic of State Finance STAN (PKN STAN) as a case study. Data were collected from a survey of 117 respondents to compare three valuation approaches: the Contingent Valuation Method (CVM), a cost-based approach, and a market-based benchmark. CVM estimation was conducted using two Ordinary Least Squares (OLS) models. The model analyzes respondents’ acceptance of an offered bid (1 = accept; 0 = reject) as a function of bid levels and demographic characteristics. The predicted acceptance probability was used to derive willingness to pay (WTP), serving as the basis for the CVM-derived rental value. The empirical results indicate that the CVM-based rental estimates are broadly aligned with values derived from the cost-based approach, while the market approach provides useful external validation for establishing a fair rental range. The findings also support the implementation of differentiated pricing strategies, such as higher rates during weekends and peak afternoon periods, to enhance both revenue optimization and facility utilization. The current research primarily contributes to the demonstration that CVM can be effectively adapted for pricing small-scale sport facility assets within PSA asset management. The research provides a methodological alternative that strengthens evidence-based decision-making and offers preliminary input for future improvements in regulatory guidelines governing state-owned asset rental valuation.